Anticoncepción quirúrgica voluntaria y factores asociados en usuarias de planificación familiar del primer nivel de atención, Iquitos 2024 - Ayambo Vela, Araceli Pamela (2024)
The objective of the study was to determine statistical association between voluntary surgical contraception and associated factors in family planning users at the first level of care in the city of Iquitos in 2024. Method: Analytical, cross-sectional, observational study; population made up of 77 users. The technique was the direct interview. Results: 69% (n=53) of the users chose AQV, while 31% (n=24) did not choose. The factors associated with the choice of AQV, with respect to sociodemographic background, were: Age (x2= 9.058; p=0.003), economic income (x2= 4.758; p=0.029); gynecological – obstetric history: Age of initiation of sexual relations (x2=9.162; p=0.002), number of pregnancies (x2=4.840; p=0.028), number of abortions (x2=6.512; p=0.011) and numbers of births (x2=8.596; p=0.003), as well as the perception of quality of care (x2=8.747; p=0.003). Concluding that, there is a statistical association between the choice of voluntary surgical contraception and the sociodemographic, gynecological-obstetric background and the perception of the quality of care.